Banana and plantain breeding - Ortíz, R.; Ferris, R.S.B.; Vuylsteke, D.R. (1995)
Despite considerable efforts of Musa improvement programmes, banana and plantain production still depends upon a limited number of landraces selected by man from the natural germplasm. Inability to replace land-races by cultivars obtained through cross-breeding creates the increased risk of epidemic disease among genetically similar cultivars. Consequently, improvement programmes have concentrated almost exclusively on resistance breeding.